Self assembled arjunolic acid acts as a smart weapon against cancer through TNF- α mediated ROS generation. Issue 2 (February 2020) - Manna, Subhankar; Dey, Aditi; Majumdar, Rakhi; Bag, Braja Gopal; Ghosh, Chandradipa; Roy, Somenath
Abstract: Arjunolic acid (AA) a plant derived pentacyclic triterpenoid which showed effective anticancer activity against MCF-7 and HeLa cells as well as no significant toxic effect was observed against normal lymphocytes. In the current study the self assemble property of arjunolic acid gives an extra emphasis on anticancer activity which was proved by several fluorescence studies like ROS generation, EtBr/AO and DAPI staining. At a selected dose of 50μg/ml AA disrupt the redox balance inside the cancer cells by producing reactive oxygen species. The apoptotic event was mediated by two key regulator proteins TNF-α and NF-κß which was proved here. The increment of the pro-inflammatory cytokines indicates the ROS mediated pathway of cancer cell apoptosis. Abstract : Biochemistry; Cell biology; Immunology; Arjunolic acid, Self assemble, Cancer cell, Apoptosis, Cytokines